Dynamic reconfiguration of distribution network considering the uncertainty of distributed generation and loads - Liu, Qi; Zhang, Lihong; Ji, Xingquan; Shi, Huizhe (Frontiers in Energy Research, 2023)
This paper presents a new methodology to perform the distribution network dynamic reconfiguration (DNDR) taking into consideration the stochastic variation of loads and distributed generation (DG) powers. To solve the heavy computational burden existed in traditional algorithms of DNDR, this study first establishes the nodal sensitivity models to calculate the nodal variations caused by the nodal power variations. Then, the DNDR is executed utilizing a co-evolutionary algorithm with the goal of loss minimization. The stochastic power flow calculations (PFC) based on the nodal sensitivity are performed in the DNDR to handle the power fluctuation of DGs and loads. Finally, the modified IEEE 33-bus test system and a practical distribution system are used for simulations. The simulation results validate the quickness and effectiveness of the proposed DNDR method.